Longitudinal Strain in Friedreich Ataxia: A Potential Marker for Early Left Ventricular Dysfunction. Issue 1 (9th July 2013) - St John Sutton, Martin; Ky, Bonnie; Regner, Sean R.; Schadt, Kim; Plappert, Ted; He, Jiwei; D'Souza, Benjamin; Lynch, David R.
<x xml:space="preserve">Abstract</x> Background Friedreich's ataxia (FRDA) is a neurodegenerative disorder resulting from deficiency of frataxin, characterized by cardiac hypertrophy associated with heart failure and sudden cardiac death. However, the relationship between remodeling and novel measures of cardiac function such as strain, and the time‐dependent changes in these measures are poorly defined. Methods and Results We compared echocardiographic parameters of cardiac size, hypertrophy, and function in 50 FRDA patients with 50 normal controls and quantified the following measures of cardiac remodeling and function: left ventricular (LV) volumes, mass, relative wall thickness (RWT), ejection fraction (EF), and myocardial strain. Linear regression analysis was used to identify significant differences in echocardiographic parameters in FRDA compared with normal subjects. In analyses adjusted for age, sex, and body surface area, significant differences were observed between parameters of remodeling (LV mass, RWT, and volumes) and function in FRDA patients compared with controls. In particular, longitudinal strain was significantly decreased in FRDA patients compared with controls (−12.4% vs. −16.0%, P < 0.001), despite similar and normal left ventricular ejection fraction (LVEF). Over 3 years of follow‐up, there was no change in strain, LV size, LV mass, or LVEF among FRDA patients. Conclusion Longitudinal strain is reduced in FRDA despite normal LVEF, indicative of subclinical cardiac dysfunction. Given late declines in LVEF in FRDA, longitudinal strain may provide an earlier index of myocardial dysfunction in FRDA.